Comparison of JET inner wall erosion in the first three ITER-like wall campaigns. (December 2021) - Krat, S.; Mayer, M.; Coad, J.P.; Lungu, C.P.; Heinola, K.; Baron-Wiechec, A.; Jepu, I.; Widdowson, A.; ,
Highlights: Rate and distribution of W erosion were the same in first 2 JET-ILW campaigns and JET-C campaigns. Rate of W erosion increased by a factor of 1.6 in the third JET-ILW campaign. Erosion of Be decreased by a factor of about 2 from JET-ILW 1 to JET-ILW 2 campaign. Erosion of Be remained unchanged from the second to the third JET-ILW campaign. Changes in Be migration and mean particle energy to the inner wall might be the reason for observed changes. Abstract: The net erosion of material from recessed areas of the JET main chamber inner wall during the first three ITER-like wall (JET-ILW) campaigns was studied using long-term samples with Be and W marker layers. The samples were analyzed using elastic backscattering spectrometry (EBS) before and after each campaign. It was found that the erosion for both Be and W was roughly homogeneously distributed in both toroidal and poloidal directions, possibly with a small maximum near the middle of the inner wall and a minimum near the bottom of the wall, as well as several toroidal distribution features. The net erosion rate of Be decreased by a factor of two between the first and the second JET-ILW campaigns, and remained unchanged during the third JET-ILW campaign. Three possible explanations are presented: a campaign to test the power handling capability of the limiter in ILW1, a change in incident particle energy distribution, and a change in limiter to divertor discharge time ratio. The net erosion rate of W remained almost unchanged through the first two JET-ILW campaigns. In the third JET-ILW campaign the net erosion rate of W from the inner wall was about 1.6 times higher than previously observed, indicating a change in the energy spectrum of particles eroding the inner wall, and the occasional addition of Kr and Xe to the fuelling.